2020
DOI: 10.1002/app.49724
|View full text |Cite
|
Sign up to set email alerts
|

Insight into color change of reversible thermochromic systems and their incorporation into textile coating

Abstract: Dynamic color and phase change of chosen thermochromic systems were deeply investigated and their incorporation into polyurethane textile coating was developed. The colorimetric properties of three commercial reversible leuco dyes-based thermochromic pigments (TPs) with activation temperature at 38, 50, and 60 C were studied. Color change as a function of temperature was evaluated and colorimetric values were related to phase transition temperatures via differential scanning calorimetry (DSC) measurement. Ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[21][22][23] For example, thermochromic microcapsules and their product lost thermochromism property when thermochromic microcapsules are exposed to sunlight even for a very short time, which greatly limits their outdoor application. 24,25 In recent decades, some reports on the stability of thermochromic materials have been carried out. Mojca Friškovec 26 found that ultraviolet rays and temperatures much higher than 150 C would make the thermochromic materials lose color, and the stability been improved by 3-4 times by treatment thermochromic fabrics with commercial UV absorbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] For example, thermochromic microcapsules and their product lost thermochromism property when thermochromic microcapsules are exposed to sunlight even for a very short time, which greatly limits their outdoor application. 24,25 In recent decades, some reports on the stability of thermochromic materials have been carried out. Mojca Friškovec 26 found that ultraviolet rays and temperatures much higher than 150 C would make the thermochromic materials lose color, and the stability been improved by 3-4 times by treatment thermochromic fabrics with commercial UV absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the activity of leuco dye to energy, thermochromic microcapsules are showing a poor heat and light stability 21–23 . For example, thermochromic microcapsules and their product lost thermochromism property when thermochromic microcapsules are exposed to sunlight even for a very short time, which greatly limits their outdoor application 24,25 . In recent decades, some reports on the stability of thermochromic materials have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochromism is the change in colour with a phase change due to temperature [1][2][3]. The functionalisation of materials that has an important role in the development of high technology takes a very large place.…”
Section: Introductionmentioning
confidence: 99%
“…The fibres used to change the colour of textiles act as a temperature indicator with the change of body temperature [10]. Thermochromic fabrics are mostly made by coating the fabric surfaces with the solution created utilising binders and microcapsules [1]. With this feature, the reproducibility made thermochromic materials significant in the making of functional fabrics [11].…”
Section: Introductionmentioning
confidence: 99%
“…The "smartness" can be based on inherent material properties, e.g. in case of thermochromics or photochromic materials, changing their color due to temperature or photo-irradiation [1,2]. Smart functions can also be implemented by integration of optical fibers [3], phase change materials [4], or the like.…”
Section: Introductionmentioning
confidence: 99%